“Kelangensih”: Karya Musik Inovatif Perpaduan Alap Bali dan Alap Hindustani - Desak Made Suarti Laksmi; I Ketut Sumerjana; I Komang Darmayuda; Jyothi Devi Krishnanandayani (Journal of Music Science, Technology, and Industry, 2023)
Pupose: Traditional Balinese vocal karawitan has a rich variety of types and variants. It also has a function and purpose that is deeply rooted as a treasure of musical art which is firmly bound by its standards. Many efforts have been made to develop it both in its integration with instrumental music and with Western musical instruments in various genres. Research methods: Several stages of creation methods such as exploration, improvisation, formation and evaluation are a creation process that produces an innovative musical work "Kelangensih". A fusion of traditional Balinese vocal style and Hindustani Classical vocal technique, combined with chamber music accompaniment as a medium of expression. By raising the theme of beauty and love, the type of Balinese hymn "Wilet Mayura" is the main work combined with Hindustani vocal technique with varied Raga processing. Raaga was chosen to enrich musical artwork in processing the melody, mood and rhythm as well as to provide wider space for the type of hymn as an aesthetic presentation for performances apart from being a religious ritual art. Result and discussion: This work provides new colors and nuances to enrich the musical treasures of Nusantara which can open up space for traditional-song singers to develop and improve their skills in working on musical works that can open new insights. Implication: This work is a new form of work using traditional material that developed creatively and innovatively. It is expected that this work will be able to reach its audience not only locally, but also regionally and transnationally. By developing this artwork into article, it has implications for the emergence of talented young creators who can encourage the growth and development of new works.